RIFM fragrance ingredient safety assessment, 1, 3-dimethyl-3-butenyl salicylate, CAS Registry Number 80118-10-1. (June 2022) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Fryer, A.D.; et al.
Highlights: 1, 3-Dimethyl-3-butenyl salicylate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.